Inglorious, Illegal Bastards : Japan's Self-Defense Force during the Cold War - Skabelund, Aaron Herald (Book collections on Project MUSE., 2022)
"A history of the post-World War II Japanese military, commonly known as the Self-Defense Force, during the Cold War."--